WeStore or AppStore: How we shop differently in mobile apps vs. social commerce - Hu, K; Karacaoglu, N (2021)
In the dynamic world of e-commerce, social commerce has emerged as a revolutionary force, transforming the ways consumers interact, explore, and purchase products online. This paper investigates the differences in customers' search and purchase patterns between a prominent online retailer's burgeoning social commerce channel—WeChat mini-program—and its native mobile app. We study customers' entire journey through a sequential search model that captures decisions from channel selection to which products to search, search termination, and final purchase. Our research contributes to the search model literature by being the first to estimate both fixed and marginal search costs in a sequential search model that leverages an omnichannel retail environment and search path data. We calculate fixed search costs, marginal search costs, and preferences for each channel and uncover differences in customers' search and purchase behaviors across channels. Our findings indicate that customers experience higher fixed search costs on WeChat, but lower marginal search costs compared to the mobile app. Additionally, customer characteristics such as historical spending levels and time of search influence their search costs. Based on these insights, we suggest two strategies tailored to each channel that leverages the differences in customers' search costs. The first strategy involves encouraging search initiation by lowering fixed search costs through peer-to-peer link sharing in the WeChat channel, while the second strategy aims to reduce marginal search costs using search-triggering coupons in the App channel. Implementing these approaches leads to a significant increase in conversion rates and profits for the online retailer. Our paper is one of the first to explore the differences between traditional retail channels and emerging social commerce channels.